A case of Listeria monocytogenes meningitis complicated by Hydrocephalus and Intraventricular hemorrhage: A review of treatment options and outcomes. (2020) - Gerstein, Shawn; Gautam-Goyal, Pranisha; Goyal, Sameer
Abstract: Listeria monocytogenes is a gram-positive bacillus known to cause various human infections including central nervous system infections. The most common central nervous system manifestations are meningitis and rhomboencephalitis, however rare complications including hydrocephalus and intracerebral hemorrhage can occur and are associated with increased mortality and incidence of lasting neurologic sequelae. The mortality ranges from 17 % to greater than 30 % in patients with neurological involvement [1–3 ]. Various case reports have studied the differing treatment approaches and outcomes of patients who experienced these complications, and there is still no consensus on optimal treatment approaches. In this paper, we report a case of Listeria meningitis complicated by both acute hydrocephalus and intracerebral hemorrhage and analyze the factors that led to a favorable outcome by reviewing the existing literature.